2010
DOI: 10.1021/jf1028448
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Content of Bioactive Substances and the Inhibitory Effects against Rat Plasma Oxidation of Conventional and Organic Hot Peppers (Capsicum annuum L.)

Abstract: The aim of this study was to evaluate the chemical compositions and antioxidative activities of hot pepper fruits cultivated with strict management by organic and conventional agricultural practices. The ascorbic acid content in the organically grown hot pepper (OGP) was significantly higher than that of conventionally grown hot pepper (CGP) in both green and red fruits. The content of other bioactive compounds such as flavonoids (apigenin, luteolin, quercetin) and total phenolics in OGP was typically higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
(54 reference statements)
2
24
0
1
Order By: Relevance
“…Organically grown sweet pepper showed significantly higher content of phenolics whatever the mature stage [78], and according to authors, this increase occurs as a response both to pathogenic pressure and to a lower nitrogen availability. Total phenolic content in organic hot peppers was higher than in conventional one [79]. In other cases [70,80], no differences were pointed out.…”
Section: Effect Of Managementmentioning
confidence: 77%
“…Organically grown sweet pepper showed significantly higher content of phenolics whatever the mature stage [78], and according to authors, this increase occurs as a response both to pathogenic pressure and to a lower nitrogen availability. Total phenolic content in organic hot peppers was higher than in conventional one [79]. In other cases [70,80], no differences were pointed out.…”
Section: Effect Of Managementmentioning
confidence: 77%
“…The vitamin C content depends on the degree of fruit ripeness. Kim et al 5 also found a significantly higher content of vitamin C in organic than in conventional pepper fruits. At the same time they observed that the vitamin C content increased during ripening in both organic and conventional fruits.…”
Section: Discussionmentioning
confidence: 91%
“…Bell pepper fruits are rich in phenolic compounds from the groups of phenolic acids and flavonoids 5, 6, 10. Organic pepper fruits were characterised by a significantly higher content of phenolic acids (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Pérez-López et al [30] found that organic peppers had the higher content of minerals, carotenoids, and antioxidant activity when compare to conventional peppers. Kim et al [31] found the same trend while Luthria et al [32] concludes that multiple analyses become critical in order to draw any specific conclusions about the influence of environment and growing conditions on phenolic content. Moreover, some studies concluded that very few compositional differences exist.…”
Section: Agricultural Systemsmentioning
confidence: 95%